Textiles and fashion from fabric construction to surface treatments - Udale, Jenny (Basics fashion design, 2023)
Introduces the processes behind creating and using textiles in fashion design. Offers an overview of the processes involved in fibre production, dyeing and finishing and also explores weaving and knitting"--Provided by publisher.